2005
DOI: 10.1128/aem.71.12.7838-7845.2005
|View full text |Cite
|
Sign up to set email alerts
|

Coaggregation Facilitates Interspecies Hydrogen Transfer between Pelotomaculum thermopropionicum and Methanothermobacter thermautotrophicus

Abstract: A thermophilic syntrophic bacterium, Pelotomaculum thermopropionicum strain SI, was grown in a monoculture or coculture with a hydrogenotrophic methanogen, Methanothermobacter thermautotrophicus strain ⌬H. Microscopic observation revealed that cells of each organism were dispersed in a monoculture independent of the growth substrate. In a coculture, however, these organisms coaggregated to different degrees depending on the substrate; namely, a large fraction of the cells coaggregated when they were grown on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
162
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(171 citation statements)
references
References 40 publications
(49 reference statements)
8
162
0
1
Order By: Relevance
“…SEM images revealed that P. thermopropionicum produced pilus-like filaments when it was grown in monocultures on fumarate and in cocultures with Methanothermobacter thermoautotropicus on propionate (Fig. 4C), as described (12). STM images and tunneling spectroscopy confirmed that these filaments were highly electrically conductive and were composed of bundles of individual electrically conductive filaments, each measuring between Ϸ10 and 20 nm in diameter (Fig.…”
Section: Production Of Nanowires Silica Hydrous Ferric Oxide (Si-hfomentioning
confidence: 62%
“…SEM images revealed that P. thermopropionicum produced pilus-like filaments when it was grown in monocultures on fumarate and in cocultures with Methanothermobacter thermoautotropicus on propionate (Fig. 4C), as described (12). STM images and tunneling spectroscopy confirmed that these filaments were highly electrically conductive and were composed of bundles of individual electrically conductive filaments, each measuring between Ϸ10 and 20 nm in diameter (Fig.…”
Section: Production Of Nanowires Silica Hydrous Ferric Oxide (Si-hfomentioning
confidence: 62%
“…NH 4 + -N in the supernatant was quantified using indophenol blue method as previously described (Tzollas et al 2010). VFAs were detected by a GC equipped with a polar capillary column (DB-FFAP, 30 m×0.25 mm×0.25 μm) and a flame ionization detector (FID) as previously described (Ishii et al 2005). The chemical compositions of the straw at initiation stage and peak II were analyzed as described previously (Hess et al 2011).…”
Section: Analytic Methodsmentioning
confidence: 99%
“…For VFAs and NH 3 -N measurements, the rumen fluid was centrifuged at 13,000 × g for 10 min. VFAs were analysed by an Agilent 6850 gas chromatograph (Agilent Technologies Inc., Santa Clara, CA, USA) equipped with a polar capillary column (HP-FFAP, 30 m × 0.25 mm × 0.25 m) and a flame ionization detector (FID), as previously described [29]. NH 3 -N in the supernatant was quantified using a continuous flow analyser (SKALAR San++, Skalar Co., Netherlands).…”
Section: Chemical Analysesmentioning
confidence: 99%